ANALISIS PELAKSANA TUGAS PEJABAT SEMENTARA (PJS) KEPALA DESA DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI TAHUN 2014 - Firnanda, Restu; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Practice Designation of Acting (PJS) in an environment of village government still maintained until now. In Kuantan Singingi even contain it in legal products, namely Singingi Kuantan District Regulation No. 4 of 2009. In Article 46 paragraph (7) states that